Penyuluhan Kesehatan Tentang Gizi Pada Perempuan Sindroma Menopause - Lusianawati, Hayu; Irmayanti, Irmayanti; Afni, Fauza; Pannyiwi, Rahmat; Andriani, Fitri; Utami, Yuri Pratiwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Abstract Menopause is the final phase where a woman's menstrual bleeding stops completely. At the age of 50 years, women enter menopause, resulting in a decrease or loss of the estrogen hormone, which causes women to experience complaints or disorders that often interfere with their daily activities and can even reduce their quality of life. Several factors that influence mothers not being ready to accept changes during menopause include education, low knowledge, work, attitudes, religion, the role of midwives, social culture and information that is still lacking. One effort to increase mothers' readiness to face menopause is to changing lifestyle and eating patterns, namely by consuming nutrients that can reduce menopausal symptoms and prevent problems that arise after menopause. The aim of this activity is to increase mothers' knowledge about balanced nutrition during menopause. The method for implementing community service activities used is in the form of counseling. After carrying out this community service activity, conclusions that can be drawn include an increase in knowledge about balanced nutrition during the menopause. The hope is that menopausal mothers can adopt a healthy lifestyle by eating nutritious food and doing physical exercise, for example seniors' exercise. By adopting a healthy lifestyle, it is hoped that the quality of life of menopausal women will be better.